Modeling of slab-on-grade heat transfer in EnergyPlus simulation program - Costa, Vanessa Aparecida Caieiro da; Roriz, Victor Figueiredo; Chvatal, Karin Maria Soares (Ambiente Construído, 2017)
The heat flow through the floor and the ground of a single-story slab-on-grade building is one of the most influential aspects in its thermal and energy performance. However, there are still many uncertainties and only few studies on the subject. This study compares different modeling alternatives of the parameters related to the heat transfer between the floor and the ground, and their influence in the thermal performance of a naturally ventilated single-story house located in São Carlos, Brazil, using the programs EnergyPlus (8.5.0) and Slab (.75). The comparison between the modeling alternatives indicated wide variation in the results. When compared with Slab, the KusudaAchenbach method of the object Ground Domain presented the largest variation, with a difference of 55.2 % in the number of degree-hours of discomfort. It was observed that even the way of using Slab - for example, with or without the convergence procedure - could cause significant differences in the results. The thermal conductivity of the soil was a parameter of great impact, resulting in differences of up to 57.5 % in discomfort. Such results provide indications of the variability and impact of the different modeling options for this type of heat transfer in EnergyPlus.